Efeito da densidade de plantio no aproveitamento da energia luminosa pelo milho (Zea mays) e pelo feijão (Phaseolus vulgaris), en culturas exclusivas e consorciadas - ALVIM, R.; Alvim, P. de T. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The study proposed to measure the primary productivity or rate of dry-matter production of maize and beans, grown under tropical conditions, in pure stands and as mixed crops at different planting densities (6.25, 12.5, 25, 50 and 100 plants/m2). Primary productivity increased in proportion to the planting densities, reaching a maximun value of 57.7 g/m2/day in the case of maize planted at 10 to 10 cm (100 plants/m2). This figure corresponded to a photosynthetic efficiency or conversion of visible solar energy of 10.5 per cent of the first month of growth, this being one of the highest figures recorded in the literature on the matter. In all densities, beans showed only about one third of the productivity and photosynthetic efficiency of maize. When grown as mixed crops, the rates of productivity of the stands were usually higher than the means for the two crops grown as single, this indicating that the decrease in assimilation rate of beans due to shading by maize was outweighted by the increase in assimilation rate of the latter as a result of reduced selfshading in the mixed stands